Synthesis and Anticonvulsant Evaluation of (R)- and (S)-3-Carbobenzyloxy-amino-1-oxysuccinimides - Lee, Do-Hun (Asian Journal of Chemistry, 2013)
A series of (R)-and (S)-3-carbobenzyloxy-amino-1-oxysuccinimides (5a-d) [(S)-3-carbobenzyloxy-amino-1-benzoyloxysuccinimde, (R)-3-carbobenzyloxy-amino-1-acetyloxysuccinimde, (R)-3-carbobenzyloxy-amino-1,4-nitrobenzoyloxysuccinimde, (R)-3-carbobenzyloxy-amino-1,4-fluorobenzoyloxysuccinimde] were synthesized and investigated their anticonvulsant activities in maximal electric shock seizure test and pentylenetetrazole induced seizure test.